Telemedicine in the clinical care of Chagas disease and American cutaneous leishmaniasis: pilot study in a public referral hospital in Brazil - Salvador, Fernanda Gonçalves Ferreira; Oliveira, Liliane Fátima A.; Pimentel, Maria Inês Fernandes; Lyra, Marcelo Rosandiski; Hasslocher-Moreno, Alejandro Marcel; Holanda, Marcelo Teixeira; Varela, Margareth Catoia; Silveira, Henrique; Valete, Cláudia Maria (Frontiers in Public Health, 2025)
BackgroundNeglected tropical diseases (NTDs) remain major public health challenge in low- and middle-income countries (LMICs), especially in rural and underserved regions. Although telemedicine has expanded globally, evidence on its implementation for individual clinical care of NTDs remains scarce. This pilot implementation study aimed to assess the feasibility and acceptability of synchronous telemedicine consultations for patients with Chagas disease (CD) and American Cutaneous Leishmaniasis (ACL) in a national reference hospital in Brazil.MethodsWe conducted a mixed-methods implementation study using the Design Science Research Methodology (DSRM). The context analysis involved structured surveys with 31 health professionals and semi-structured interviews with two local managers. Patients diagnosed with CD or ACL were recruited from August to October 2024. Teleconsultations were performed via WhatsApp video calls by four specialists. Patient satisfaction was evaluated using structured questionnaires.FindingsOf the 46 patients recruited, 38 (82.6%) completed teleconsultations. Most were older adults and had no prior telehealth experience. Despite low digital literacy and education levels, 63.2% (24/38) completed the teleconsultation without assistance. High levels of satisfaction were reported: 97.4% (37/38) were satisfied and would attend future virtual visits. Participants reported the reduced travel burden and improved access to care. No major technical issues were observed.ConclusionSynchronous telemedicine via a low-cost, widely available platform was feasible and well-accepted for clinical follow-up of CD and ACL in a Brazilian public hospital. This approach may help reduce access barriers to specialized care for NTDs. Further research should evaluate clinical outcomes and cost-effectiveness in LMIC settings.